2023
DOI: 10.3389/fped.2023.1104728
|View full text |Cite
|
Sign up to set email alerts
|

Early vasopressin infusion improves oxygenation in infants with congenital diaphragmatic hernia

Abstract: ObjectiveCongenital Diaphragmatic Hernia (CDH) is a complex disease including a diaphragmatic defect, lung hypoplasia, and pulmonary hypertension. Despite its increasing use in neonates, the literature on the use of vasopressin in neonates is limited. The aim of this work is to analyze the changes in clinical and hemodynamic variables in a cohort of CDH infants treated with vasopressin.MethodsAmong CDH infants managed at the Neonatal Intensive Care Unit (NICU) of our hospital from May 2014 to January 2019, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…More recent clinical studies confirmed the efficacy of AVP as a rescue treatment in neonates with PPHN and catecholamine refractory hypotension [79,85,[164][165][166][167][168]. Common findings of these studies were the increase in AP and improvement in oxygenation and requirements for inotropes following the addition of AVP to the treatment regime.…”
Section: Vasopressin and Terlipressinmentioning
confidence: 83%
See 1 more Smart Citation
“…More recent clinical studies confirmed the efficacy of AVP as a rescue treatment in neonates with PPHN and catecholamine refractory hypotension [79,85,[164][165][166][167][168]. Common findings of these studies were the increase in AP and improvement in oxygenation and requirements for inotropes following the addition of AVP to the treatment regime.…”
Section: Vasopressin and Terlipressinmentioning
confidence: 83%
“…Common findings of these studies were the increase in AP and improvement in oxygenation and requirements for inotropes following the addition of AVP to the treatment regime. Additional findings included reduction in lactic acidosis [79], avoidance of extracorporeal membrane oxygenation in 50% of the patients [164], and improved NIRS findings [167].…”
Section: Vasopressin and Terlipressinmentioning
confidence: 99%
“…71 Capolupo et al reported a cohort of 27 patients with isolated CDH and found that early initiation of vasopressin improved OI and near-infrared spectroscopy after 12 and 24 hours of infusion. 72 Norepinephrine has been employed to improve the SVR/PVR ratio and oxygenation in infants with severe PHT. 73 Research conducted by Tourneux et al, encompassing a group of 18 neonates with severe PHT, demonstrated an increase in systemic pressure and LVO, alongside a 20% rise in mean left pulmonary artery blood flow velocity.…”
Section: Vasopressorsmentioning
confidence: 99%